(untitled) (PERcursos Linguísticos, 2020)
The purpose of this communication is to analyze President Jair Bolsonaro’s pronouncements in his daily contact with reporters outside the Palacio da Alvorada in Brasilia, baptized by his advisors of "Talkey shows". We will focus on two episodes that explain the degree of breakdown in the relationship between journalists and the head of the national executive. The "scoop" episode, aimed at journalist Patrícia Campos Melo, from Folha de S. Paulo, and the bananas offered to reporters by a comedian during a "talkey show", in February and March of this year, respectively. We will use the theoretical tools of Critical Discourse Analysis, a theoretical aspect that postulates the social use of language in interactions in which power relations and domination are established by economic and political groups that use language as a form of social control, through various forms of discursive practices, such as mockery and demonization of the press. We use as theoretical references Van Dijk (1990, 2009, 2017), Fairclough (2003), Charaudeau (2003) and Fonseca (2010), among others, using linguistic tools to analyze the relationships between language, power and social control.